Gym exercising patterns, lifestyle and high-risk sexual behaviour in men who have sex with men and in heterosexual men. Issue 11 (24th November 2014) - Mor, Z; Parfionov, K; Davidovitch, N; Grotto, I
Abstract : Objective: Lifestyle may be associated with risk behaviours. This study compares gym exercise and sexual risk behaviour between men who have sex with men (MSM) and heterosexual men. The research was based on the assumption that men who become muscular and physically attractive increase their number of sex partners and consequently their risk of HIV or other sexually transmitted infections (STIs). Setting: Five gyms in central Tel Aviv, Israel. Participants: In 2012, a sample of 182 (48%) MSM and 197 (52%) heterosexual men who train in gyms completed anonymous questionnaires regarding their training, health and sexual behaviours. Outcomes: Participants in this cross-sectional study who exercised more than the median number of anaerobic training hours were defined as performing intensive anaerobic training (IAT), and those who had performed more than one act of unprotected anal/vaginal intercourse in the preceding 6 months with a partner whose HIV status was unknown were defined as high risk. Results: MSM showed a stronger desire to become muscular than heterosexual men, were more likely to perform IAT, and used protein powders or anabolic steroids. They reported that improving their body shape and increasing their self-confidence were their main reasons for training, whereas heterosexual men indicated weight loss and health improvement as the main reasons for training. MSM engaged in riskier sexual behaviour than heterosexual men. Of all the high-risk men, 61.9% (N=70) performed IAT, while 38.1% (N=43) performed moderate anaerobic training (p<0.01). The association between IAT and sexual risk was stronger in MSM than in heterosexual men (p<0.01 vs p=0.05, respectively). The interaction between MSM and IAT in high-risk participants was multiplicative. Conclusions: MSM practised more IAT than heterosexual men, and their interaction between IAT and sexual risk was multiplicative. The MSM community could benefit from a holistic approach to sexual health and its association with body image and IAT. The gym MSM culture demonstrates how internal dynamics and social norms are possible factors driving MSM to high-risk behaviour for HIV/STI. Study registration: The study was approved by the Wolfson Hospital Review Board, Holon, Israel (WOMC-0058-09).